Lead content in deciduous teeth of children in Quezon City - Jose, Ma. Alessandra A.
This is a pilot study which aims to describe the lead content levels in deciduous teeth of children in Quezon City. Twenty (20) deciduous teeth were randomly collected from various clinics in Quezon City from October to January 1993. These teeth were dissolved in nitric acid and analyzed by flamed atomic absorption spectrophotometry. Tooth lead levels ranged from 2.16 ug/g - 5 ug/g (mean: 3.44 ug/g; standard deviation: + .87 ug/g). This mean lead level was statistically compared with and found to be different from other countries such as Germany and the United Kingdom. Since lead is accumulated in teeth, determination of lead content of deciduous teeth may provide a useful index to previous lead exposure.